(untitled) (Research, Society and Development, 2020)
This study aims to analyze the changes brought about by neoconstitutionalism in legal-constitutional theory, notably the phenomenon of constitutionalization of law and the subjection of branches of legal science to the new constitutional hermeneutic dogma. For this reason, the existence of a Constitutional Criminal Law was defended and, consequently, the need for the interpretation and application of criminal rules to previous constitutional conformity. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of bibliographic-documental data, proceeded in order to carry out a re-reading of the principle of criminal legality to make it ponderable before the specific case, in which is dysfunctional. However, it also clarified about the functions of fundamental rights as limits to state intervention, the application of the principle of proportionality in the event of collision between constitutional norms and the incidence of the principle of the prohibition of deficient protection in face of criminal legality. Finally, in view of the exposed problem, it was sought, based on constitutional principles, to clarify the need of the State, based on the defense of human rights and respect for social well-being, in the face of the existence of cases of difficult solution in the criminal sphere whose traditional interpretation methods do not achieve a satisfactory result, use the theory of defeatability to overcome the original normative standard, in order to preserve the victim’s human dignity and the effectiveness of criminal jurisdiction.